Combined periodontic-orthodontic-endodontic interdisciplinary approach in the treatment of periodontally compromised tooth - Deepa D; Mehta D; Puri Viren; Shetty Sadashiva (Wolters Kluwer Medknow Publications, 2010)
Orthodontic treatment in adult patients is one of the most frequently encountered components involving multidisciplinary approaches. In the present report, a 28-year-old male patient was treated for localized chronic periodontitis with pocket formation, mobility, pathologic migration and malalignment of maxillary left lateral incisor tooth #22. The periodontal therapy included motivation, education and oral-hygiene instructions (O.H.I.), scaling and root planing and periodontal flap surgery. Subsequently on resolution of periodontal inflammation, orthodontic therapy was carried out using the orthodontic aligner for a period of 6 months. Post-treatment (3 years) results showed complete resolution of infrabony pocket with significant bone fill, reduced tooth mobility and complete alignment of the affected maxillary left lateral incisor, thus restoring the esthetics and function.